The Horizons of Medieval French and Occitan : New Approaches to Manuscripts and Texts - Campbell, Emma; Sunderland, Luke (Explorations in Medieval Culture, 2026)
This volume celebrates Simon Gaunt's scholarship by exploring the current boundaries and future directions of medieval French and Occitan literary criticism. The essays address questions of vital importance to these disciplines, including: What are the literary cultures and identities associated with supralocal vernacular languages? How do medieval manuscripts construct authorship, gendered identity, and voice in ways that range across genres and expressive registers? How do such codices mediate sensory experience and connect the textual, the visual, and the aural? How do French and Occitan texts negotiate the agencies of human and nonhuman bodies, and theorize emotions, sacrifice, and affect? Contributors are William Burgwinkle, Philippe Frieden, Jane Gilbert, Miranda Griffin, Alice Hazard, Thomas Hinton, Melek Karataş, Sarah Kay, Matthew Siôn Lampitt, Catherine Léglu, Peggy McCracken, Robert Mills, David Murray, Linda Paterson, Karen Pratt, Henry Ravenhall, and Simone Ventura.